Response of growth, yield, and seeds quality of G0 potato on different potassium fertilizer doses and retardant concentrations in Jatinangor medium land - Ramadhani, Selika Fitrian; Donita, Yukta Alvira; Nuraini, Anne; Kadapi, Muhamad (Universitas Padjadjaran, 2024)
This study aims to determine the best interaction of potassium (K) fertilizer dose and retardant concentration on the growth, yield, and seed quality of G0 potato grown in the medium land of Jantinangor. The experiment was conducted at Screen House Station Ciparanje, Jatinangor, Faculty of Agriculture Universitas Padjadjaran from November 2022 until January 2023 at an elevation of ± 685 meters above sea level. The experimental design used was the Factorial Randomized Block Design (RBD). The first factor was the K fertilizer dose including 50%, 100%, and 150%. The second was the retardant concentration including without retardant, 100 ppm paclobutrazol, 100 ppm prohexadione-Ca, and 150 ppm prohexadione-Ca. The experimental results showed that there was an interaction effect between the K dose and retardant concentration. The interaction effect of 150% K and 100 ppm prohexadione-Ca showed the highest percentage of L class seed tuber and the lowest tuber weight loss. Independently, 150% K improved growth rate, number of tubers (6.67 knol/plant), and weight of tubers (73.33 g/plant). Independently, 100 ppm paclobutrazol concentration increased the chlorophyll content index. 150 ppm prohexadione-Ca concentration suppressed leaf area and plant height but increased stomatal conductance, fast emergence shoot time, and shoot length. 100 ppm prohexadione-Ca concentration produced the highest number of tubers and the weight of tubers, i.e., 6.78 knol/plant and 74.33 g/plant, respectively.